COVID-19 And Declines in The Number of Passengers Transported by Air in Europe - Bartosz KOZICKI; Szymon MITKOW; Paweł JAŚKIEWICZ and Bogdan SOWA (Communications of International Proceedings, 2021)
In this study the research was related to the declines in the number of passengers transported by air in 29 European countries under consideration in 2020. The research is based on secondary data taken from the Eurostat website. The research used the Holt-Winters method to forecast data on the number of passengers transported by air in 29 respective European countries between 2011-2019 for 2020. The declines were examined on the basis of a comparative analysis and calculated indices as dynamics indices with a fixed and non-fixed basis.
Keywords: Transport; Forecasting; Economic Security; COVID-19.